Inverse Design of Incoherent Raman Pump Sources for U-Band WDM Transmission Over 125 km G.652.D Fiber - Tangyanjun Lan; Junjiang Xiang; Gai Zhou; Meng Xiang; Songnian Fu; Yuwen Qin (IEEE Photonics Journal)
The ever-increasing demand for the transmission capacity has stimulated intensive investigations, in terms of both new transmission window of standard single mode fiber (SSMF) and new fiber utilizing the spatial domain. Multi-band wavelength division multiplexing (WDM) transmission exploring the extended wavelength band, besides traditional C+L band, is an attractive solution for the rapid and cost-effective enhancement of transmission capacity. To this end, here we demonstrate the U-band WDM transmission over 125-km G.652.D fiber, when the C-band amplified spontaneous emission (ASE) source acts as the incoherent pump for Raman amplification (RA). Meanwhile, bidirectional long short-term memory neural network (BiLSTM-NN) is applied to inversely design the spectral shape of two C-band ASE sources. After the optimization through inverse design, the ROP variation at the U-band can be less than 1.2 dB under different net Raman gains. Consequently, we can experimentally achieve a net Raman gain of ∼15 dB over a 3 dB bandwidth of around 2.1 THz at the U-band, under the condition of distributed bidirectional Raman pump configuration. Finally, the performance of the U-band RA is experimentally verified by transmitting three-wavelength 20 GBaud DP-QPSK signals, when the threshold of 7% HD-FEC can be successfully reached.